A novel marker in pregnant with preeclampsia: renalase. (3rd April 2017) - Yılmaz, Zehra Vural; Akkaş, Elif; Yıldırım, Tolga; Yılmaz, Rahmi; Erdem, Yunus
Abstract: Background : Preeclampsia is characterized by an increase in high blood pressure and decrease in GFR and proteinuria, however, the underlying mechanisms are still unclear. Renalase is a recently discovered protein implicated in regulation of blood pressure in humans. Materials and methods : Plasma concentrations of serum renalase were measured in healthy controls, healthy pregnant and pregnant with preeclampsia matched for age, gestational age, in the third trimester of pregnancy. Serum renalase levels were compared in pregnant with and without preeclampsia and non-pregnant controls. Factors associated with serum renalase levels in pregnancies were also evaluated. Results : In healthy pregnant serum renalase levels were significantly higher than in controls. However, pregnant with preeclampsia had lower renalase levels than healthy controls. Serum renalase levels were inversely associated with blood pressure levels and positively correlated with glomerular filtration rate. Conclusion : The results indicated that the development of preeclampsia in pregnant is accompanied by altered serum renalase levels. High blood pressure and kidney damage that characterize this disorder are mediated at least in part by low renalase levels.